WordPress for dummies - Sabin-Wilson, Lisa (--For dummies., 2010)
The bestselling guide to WordPress, fully updated for newest version of WordPress. WordPress, the popular, free blogging platform, has been updated with new features and improvements. Bloggers who are new to WordPress will learn to take full advantage of its flexibility and usability with the advice in this friendly guide. Previous editions have sold nearly 50,000 copies, and interest in blogging continues to explode.: WordPress is a state-of-the-art blog platform that emphasizes aesthetics, Web standards, and usability; WordPress For Dummies, 3rd Edition covers both the free-hosted WordPress.